CeO2 based catalysts for elemental mercury capture - Zhao, Haitao; Yin, Shufan; Chen, Quhan; Huang, Xingduan; Chen, Hongkun; Lu, Lu; Zheng, Chenghang; Gao, Xiang; Wu, Tao (Elsevier, 2019)
The alternative materials to remove Hg 0 from energy utilization sectors is crucial to mercury control in atmosphere. CeO2 based catalysts were prepared by an incipient wetness impregnation (IWI) method. A novel Hg 0 and Hg T temperature-programmed surface reaction (Hg 0 -Hg T -TPSR) was proposed in this study for the investigation of the prepared CeO2 based catalysts with the qualitative and quantitative analyses. The characteristic temperatures, the areas of adsorption region and desorption region, and activation energy with reaction kinetics were investigated to evaluate the performance. It was found that 2wt% Ce catalyst has the best mercury removal performance with the highest Hg 0 removal ability and the lowest Ea. There was also small amount of Hg 2+ detected which indicated the catalytic effect contributed. The results suggested that 2wt% Ce based binary catalysts could be the potential candidates to be investigated in the future study. © 2019 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/) Peer-review under responsibility of the scientific committee of ICAE2018 - The 10th International Conference on Applied Energy.